2009
DOI: 10.1007/s11274-009-0103-6
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of alkaline protease production in Bacillus circulans using plasmid transformation

Abstract: Plasmid transformation is an efficient and crucial biotechnological tool that enables the enhancement of many important microbial characters that would be beneficial in a lot of industrial, agricultural and environmental applications. In the present study, five Bacillus species (B. subtilis, B. cereus, B. alvei, B. circulans and B. pumilus) were investigated. They were isolated from agricultural soils of different local arid environments of the Kingdom of Saudi Arabia, identified and characterized for their pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…The increase in productivity of the alkaline protease by the transformants may be attributed to the donor plasmid harboring the apr gene. In this context, previous reports were in support of these findings (Jorgensen et al, 2000;Sabir et al, 2009), indicating that the increase in gene copy number enhances the enzymatic production. The maximum crude enzyme activity of alkaline protease in B. licheniformis CICIM B5102 was 3,505 U/ml after 96 h, whereas that of the recombinant B. amyloliquefaciens strain D was 4,926 U/ml after 60 h. More transformants were selected for the shaker flask fermentation test to obtain higher protease production.…”
Section: Construction Of the Recombinant B Amyloliquefacien And Imprsupporting
confidence: 72%
“…The increase in productivity of the alkaline protease by the transformants may be attributed to the donor plasmid harboring the apr gene. In this context, previous reports were in support of these findings (Jorgensen et al, 2000;Sabir et al, 2009), indicating that the increase in gene copy number enhances the enzymatic production. The maximum crude enzyme activity of alkaline protease in B. licheniformis CICIM B5102 was 3,505 U/ml after 96 h, whereas that of the recombinant B. amyloliquefaciens strain D was 4,926 U/ml after 60 h. More transformants were selected for the shaker flask fermentation test to obtain higher protease production.…”
Section: Construction Of the Recombinant B Amyloliquefacien And Imprsupporting
confidence: 72%
“…from fish which was capable of producing protease enzyme. Sabir et al (2009) reported that, B.subtilis was the best protease producer among the tested strains. In the present study, all the bacterial species isolated had a better potentiality of degrading market fish wastes.…”
Section: Discussionmentioning
confidence: 96%